COVID-19 disease treatment: pivotal challenges in the arena of umbilical cord-mesenchymal stem cells (UC-MSCs) - Soliman, Al-Hassan; Abdellatif, Mohamed (Frontiers in Cell and Developmental Biology, 2023)
The 2019 new coronavirus disease (2019-nCoV) outbreak was a terrible incidence in the 21st century. The outbreak has led to unprecedented economic and health shortages. Unfortunately, there are no effective methods to cure COVID-19. However, many studies have proposed promising results using cell-based therapies such as umbilical cord mesenchymal stem cells (UC-MSCs). The efficacy of UC-MSCs as a potential treatment for patients with COVID-19 has been widely investigated. Cytokine release syndrome or cytokine storm is caused by vast numbers of immune cells producing pro-inflammatory cytokines in a positive feedback loop and is one of the key elements contributing to the mortality and morbidity of COVID-19. Using UC-MSCs has proven to ameliorate and immunomodulate the release of these cytokines that allow them to regulate both adaptive and innate immune responses. The purpose of this review is to evaluate and shed light on the efficacy of UC-MSCs in patients with COVID-19-induced ARDS.